Muslim Religious Openness and Ilm: Relationships with Islamic Religious Reflection, Religious Schema, and Religious Commitments in Malaysia - Ismail, Nik Ahmad Hisham; teke, mustafa; Watson, Paul; Chen, Zhou (Brill Academic Publishers, 2015)
Religious Reflection Scales yield cross-cultural data suggesting that religious traditions have potentials to integrate intellect with faith. This investigation extended analysis of that possibility to Sunni Muslim university students in Malaysia (N =211) and also examined the hypothesis that Islamic commitments to knowledge (Ilm) promote religious openness. Faith and Intellect Oriented Religious Reflection correlated positively and predicted openness. The Truth of Texts and Teachings factor from the Religious Schema Scales essentially assesses a form of fundamentalism and displayed direct linkages with religious openness as well. Ilm factors from the Ummatic Personality Inventory correlated positively with religious openness and mediated associations of Islamic Religious Reflection with other constructs. Quest as a presumed index of religious openness proved to be incompatible with sincere Muslim commitments. These findings supplemented previous Muslim, Christian, and Hindu data in confirming the potential openness of religious traditions.